Gastroprotective mechanism of modified lvdou gancao decoction on ethanol-induced gastric lesions in mice: Involvement of Nrf-2/HO-1/NF-κB signaling pathway - Xie, Lei; Luo, Minyi; Li, Junlin; Huang, Wenguan; Tian, Guangjun; Chen, Xiuyun; Ai, Ying; Zhang, Yan; He, Haolan; Jinyang He, (Frontiers in Pharmacology, 2022)
Modified Lvdou Gancao decoction (MLG), a traditional Chinese medicine formula, has been put into clinical use to treat the diseases of the digestive system for a long run, showing great faculty in gastric protection and anti-inflammatory, whereas its protective mechanisms have not been determined. The current study puts the focus on the protective effect and its possible mechanisms of MLG on ethanol-induced gastric lesions in mice. In addition to various gastric lesion parameters and histopathology analysis, the activities of a list of relevant indicators in gastric mucosa were explored including ALDH, ADH, MDA, T-SOD, GSH-Px, and MPO, and the mechanisms were clarified using RT-qPCR, ELISA Western Blot and immunofluorescence staining. The results showed that MLG treatment induced significant increment of ADH, ALDH, T-SOD, GSH-Px, NO, PGE2 and SS activities in gastric tissues, while MPO, MDA, TNF-α and IL-1β levels were on the decline, both in a dose-dependent manner. In contrast to the model group, the mRNA expression of Nrf-2 and HO-1 in the MLG treated groups showed an upward trend while the NF-κB, TNFα, IL-1β and COX2 in the MLG treated groups had a downward trend simultaneously. Furthermore, the protein levels of p65, p-p65, IκBα, p-IκBα, iNOS, COX2 and p38 were inhibited, while Nrf2, HO-1, SOD1, SOD2 and eNOS were ramped up in MLG treatment groups. Immunofluorescence intensities of Nrf2 and HO-1 in the MLG treated groups were considerably enhanced, with p65 and IκBα diminished simultaneously, exhibiting similar trends to that of qPCR and western blot. To sum up, MLG could significantly ameliorate ethanol-induced gastric mucosal lesions in mice, which might be put down to the activation of alcohol metabolizing enzymes, attenuation of the oxidative damage and inflammatory response to maintain the gastric mucosa. The gastroprotective effect of MLG might be achieved through the diminution of damage factors and the enhancement of defensive factors involving NF-κB/Nrf2/HO-1 signaling pathway. We further confirmed that MLG has strong potential in preventing and treating ethanol-induced gastric lesions.